MEDICAL LIFE OF SOCIETY: STRUCTURE, CHARACTERISTICS AND PROPERTIES (Web of Teachers: Inderscience Research, 2025)
This scientific article analyzes the concept of society from a socio-philosophical perspective, comprehensively substantiates the existence of the medical life of society. Its ontological nature and epistemological characteristics are revealed. At the same time, the specific structure of the medical life of society, the essence and content of the concepts of health and illness, and the need to develop the concept of "Smart Medicine" are also shown.